LDL receptor related protein 1 is an adverse prognostic biomarker that correlates with stromal remodeling and macrophages infiltration in bladder cancer - Du, YiHeng; Liu, YiZheng; Cao, Jin; Jiang, Xiang; Wang, Yi; Yu, Jiang; Wang, Bo; Wang, XiZhi; Xue, BoXin (Frontiers in Immunology, 2023)
Bladder cancer (BLCA) is a highly heterogeneous disease that is influenced by the diverse tumor microenvironment. While immune checkpoint blockade (ICB) therapy has been approved for advanced BLCA, patients' response to this treatment can be affected by the tumor microenvironment. Therefore, it is essential to conduct further research on the tumor microenvironment to identify molecular markers and therapeutic targets that can improve BLCA treatment. In this study, we aimed to investigate the prognostic significance of LRP1 in BLCA by analyzing TCGA and IMvigor210 cohorts. We utilized gene mutation analysis and enrichment to identify LRP1-associated mutated genes and biological processes. Deconvolution algorithms and single-cell analysis helped us understand the tumor-infiltrated cells and biological pathways associated with LRP1 expression. Immunohistochemistry was also conducted to validate the bioinformatics analysis. Our results revealed that LRP1 was an independent risk factor for overall survival in BLCA patients and was associated with clinicopathological features and FGFR3 mutation frequency. Enrichment analysis demonstrated that LRP1 was involved in extracellular matrix remodeling and tumor metabolic processes. Furthermore, the ssGSEA algorithm revealed that LRP1 was positively correlated with the activities of tumor-associated pathways. Our study also found that high LRP1 expression impaired patients' responsiveness to ICB therapy in BLCA, which was predicted by TIDE prediction and validated by IMvigor210 cohort. Immunohistochemistry confirmed the expression of LRP1 in Cancer-Associated Fibroblasts (CAFs) and macrophages in the tumor microenvironment of BLCA. Our study suggests that LRP1 may be a potential prognostic biomarker and therapeutic target in BLCA. Further researches on LRP1 may improve BLCA precision medicine and enhance the efficacy of ICB therapy.